Carbon dioxide sequestration in cementitious construction materials - Pacheco-Torgal, F. (2018)
Carbon Dioxide Sequestration in Cementitious Construction Materials provides an updated, state-of-the-art review on the development of cementitious construction materials based on carbon dioxide storage, which will have a major eco-efficient and economic benefit for the construction industry. Key chapters include methods for the assessment of carbon dioxide absorbed by cementitious materials, air and water-based carbon dioxide storage, carbon dioxide storage modeling, carbonation mechanisms, carbon dioxide storage on recycled aggregates, calcium, sodium and magnesium- based binders, properties and the durability of carbon dioxide based concrete. Promotes the importance of CO2 storage in carbonation of these materials, especially reincorporation of CO2 during fabrication. Discusses a wide range of cementitious materials with CO2 storage capabilities. Features redesign of cementation mechanisms to utilize CO2 during fabrication